The implementation and evaluation of a nutrition education programme developed for caregivers - Ochse, Catharina Elizabeth (Vaal University of Technology, 2016)
Background South Africa is one of the developing countries faced with the co-existence of undernutrition and overnutrition, often experienced within the same household. On the one hand, hunger, undernutrition and micronutrient deficiencies are linked to poverty and household food insecurity. Simultaneously, South Africans are exposed to ‘nutrition in transition’, where overweight and chronic diseases of lifestyle, such as diabetes mellitus, cardiovascular diseases and cancer are on the rise as part of the overnutrition profile. Sound nutrition is important throughout the lifecycle to combat under- and overnutrition and nutrition-related diseases. In urban areas, the grandmother or another senior female family member is often responsible for caring for the children in the household during the day. This includes physical, emotional and nutritional care. It is therefore essential for the caregiver to have good nutrition knowledge, to provide not only in her own needs, but also in those of the children. A nutrition education programme is one strategy for improving the nutrition knowledge of caregivers of children. Objective The primary objective in this study was to develop, tailor, implement and evaluate a nutrition education programme (NEP) for Sesotho-speaking females and caregivers of children in the Boipatong Township in the Vaal Region of South Africa and to test its impact in the short and longer term. Nutrition knowledge regarding four South African food-based dietary guidelines (FBDGs) was empirically tested before and after the intervention and then compared to a control group. In addition, dietary intake was assessed to detect any changes after the intervention in the medium term. Methodology In this both quantitative and qualitative methodologies were applied. Two frameworks, the United Nations Children’s Fund (UNICEF) Framework of Malnutrition (2004) and the Food and Agriculture Organisation (FAO) Framework for Nutrition Education (1997), gave structure to the planning, implementation and evaluation of the research project. This study’s nutrition education programme was based on a socio-ecological model to guide behavioural change in terms of healthy food choices. In the preparation phase, a situational analysis was performed by means of a cross-sectional analytical design using descriptive statistics. Socio-demographic and self-reported health information was obtained. Nutrition knowledge, based on the South African food-based dietary guidelines (FBDGs), was measured, and dietary intake was assessed and compared with the estimated average requirements (EARs) for their age categories. Phase two, the formulation phase, used an experimental design. The acceptability and understanding of the existing national nutrition education (NE) material for individuals with low living standards (LSM) was investigated in this phase of the nutrition education programme (NEP). A culturally tailored booklet was developed in English, translated into Sesotho, pilot tested and implemented as part of the nutrition education programme. Lesson plans were developed and pilot tested. A non-randomised control trial was used in the implementation and evaluation phases. The effect of the nutrition education programme on nutrition knowledge was quantitatively measured in a pre- and post-test design at each discussion session in the short term, using paired t-tests in the experimental group of caregivers. The evaluation phase tested the impact of the nutrition education in the longer term. Nutrition knowledge was measured quantitatively in a before-after intervention test design by means of a self-completed structured questionnaire, based on the four South African FDBGs included in the programme. A control group who was not subjected to any intervention was used to complete the same questionnaire before and after the intervention in the same time period as the experimental group. In the experimental group, dietary intake was assessed before and after the intervention to detect changes in dietary intake. No dietary intake was measured in the control group, as changes could be attributed to influences beyond the control of this study. Two randomly selected focus groups of the experimental group were run to provide deeper insight into their perceptions regarding the acceptability and understanding of the NEP and NE material. Results The situational analysis of the preparation phase revealed a poor community that displayed typical patterns of nutrition in transition, at risk of malnutrition. The median age of the sample of caregivers was 44 years (IQR 32-62). Income and consumption poverty was confirmed by 80.5 percent of households spending R300 or less on food, with 75 percent of households having between four and seven people living in the dwelling. Dietary results were indicative of food poverty and poor food choices, possibly due to monetary constraints. A low energy intake (median 5323 kJ/day; IQR 3369-7949), was observed. Only 13.9 percent reached the estimated energy requirement (EER) of 7855 kJ per day for their age category. The overall mean average requirements of the diet was 0.7 but the possiblity of micronutrient deficiencies could not be excluded with a MAR of 0.6 for vitamins and minerals respectively. The median nutrition knowledge was 50 percent (IQR 42-54%) The lowest score was obtained for the FBDG ‘Enjoy a variety of food’ (33.4%; 95% CI 1.1), followed by the FBDG on animal protein (40.3%; 95% CI 1.0). It was decided to augment these two FBDGs with the plant protein FBDG (54.3%; 95% CI 1.8). Despited a relatively good knowledge measured in the caregivers, none of the plant protein food items appeared in the top 20 food items most frequently consumed. The formulation phase included the testing of existing nutrition education material. Messages were well understood (60.5%). However, caregivers found the images contained in the pamphlets and the design of the pamphlets confusing. A definite need was identified for new, culturally acceptable NE material in the caregivers’ home language, Sesotho (74%). During the implementation phase the lectures were presented and the change in the short-term nutrition knowledge of the FBDGs was measured at every session by means of a pre-post-test design. The median age of the caregivers was 63 years (52-78). A significant change in nutrition knowledge was found for each FBDG in terms of the mean number of questions answered correctly by the participants between the results of each pre- and post-test. In the evaluation phase, the impact of the NEP was measured in the Boipatong experimental group and compared, regarding nutrition knowledge, to a control group in the longer term (three months after completion of the intervention). Median nutrition knowledge before the intervention was 49 percent (IQR 46-57) compared to 70 percent (IQR 68-73) after the intervention – an increase of 21 percent. In contrast, the control group showed an increase of only five percent. The results showed that the eating habits of many of the caregivers still fell substantially short of internationally recognised standards (estimated energy requirement (EER) and estimated average requirement (EAR)), and this could contribute to undernutrition as well as to an increased risk of diet-related chronic disease. A median kilojoule intake of 4788 kJ (IQR 3415-6596) per day before and 4651 kJ (IQR 3369-6664) per day after the intervention was registered. Carbohydrate foods remained an important source of energy. Calcium presented a major concern, as none of the participants reached the EAR despite a slight increase in the intake of milk (volume and frequency) after the intervention, as validated by the top 20 food lists and as measured by a nutrient average requirement (NAR) of 0.1 to 0.7 before and after the intervention respectively. The mean average requirements (MAR) remained relatively stable, at 0.7 (median) before the intervention and 0.6 after the intervention. The NEP thus had an insignificant positive effect on dietary intake, except for calcium, iodine and vitamin C intake, which showed significant increases. No relationships could be found between the MAR as an indicator of dietary quality and nutrition knowledge. However, this does not mean that an NEP is not a suitable strategy. Changes in food choices and dietary intake should be measured in the longer term, since lifestyle changes are challenging to adopt when people, especially those in deprived communities, do not have the financial means to make healthy food choices. Conclusion When planning nutrition education strategies to improve the health status of communities in deprived areas, one is faced with the difficulty of households with a low socio-economic status and poor dietary intake, which increases the risk of food and nutrition insecurity. The nutrition education programme, developed, tailored and implemented as an intervention strategy to address an identified need of caregivers, was effective in improving nutrition knowledge. Four of the South African dietary guidelines were used in the nutrition education programme tailored to the specific profile that emerged from the situational analysis and the development of supportive nutrition education material. Lesson plans and the Sesotho and English booklets are available for use in other nutrition education programmes. The study contributed to the understanding of food choices of the urban community of Boipatong as well as of the nutrient inadequacies observed. Nutrition knowledge alone is not enough to bring about changes in food choices when the means to do so are lacking. Poverty and nutrition are closely linked and thus difficult to separate.
D. Tech. (Food Service Management, Department of Hospitality, Tourism and PR Management, Faculty of Human Sciences)|, Vaal University of Technology|
Keywords: Undernutrition in South Africa; Overnutrition in South Africa; Micronutrient deficiencies; Nutrition education programme; Unicef Framework of Malnutrition; FAO Framework for Nutrition; Healthy food choices; 614.59390968; Nutrition -- Evaluation.; Nutrition education.; Dissertations, Academic -- South Africa.